Hidden populations: discovering the differences between the known and the unknown drug using populations in the Republic of Georgia - M. Gogia; C. Lawlor; N. Shengelia; K. Stvilia; H. F. Raymond (BMC, 2019)
Abstract Background The HIV epidemic in Georgia is increasing. Data shows that compared to previous years, Georgia has increasingly more HIV-infected individuals than previous assessments. Select client groups remain hard to reach by harm reduction programs. The need for innovative strategies to involve these individuals is imperative. Methods The following study examines demographics and risk factors of participants, previously known and not known to harm reduction services, for HIV and other infectious disease in towns across Georgia in 2015 and compares risk among different groups, while also assessing the rationale for implementing Peer-Driven Interventions in Georgian Harm Reduction activities. Important differences in demographics and risk profile are thought to exist between those exposed, and those unexposed, to harm reduction activity. Results Important and striking differences between previously known and unknown participants, including demographic background and risk profile and behaviours exist in the drug using community. These differences can potentially explain some of the rise of HIV prevalence in Georgia. Conclusion Significant differences exist between known and unknown drug users in Georgia, the differences between which are crucial for planning future and holistic harm reduction activities in Georgia, regionally and globally. The research advocates for smarter harm reduction activity, adds to the global evidence for the utility of Peer-Driven Intervention, and encourages sustained global effort for reduction of blood-borne disease burden globally.